Llustrated animal stories from the qur'an - Dr abdur rauf (Ferozsons (Pvt) Limited ; Lahore, 2019)
Illustrated Animal Stories from the Qur'an brings to life captivating tales of animals in Islamic tradition, teaching moral lessons through beautiful illustrations.